Breaking barriers to cloud customer choice: Unlocking Europe's AI and innovation leadership - Matthias Bauer; Andrea Dugo; Dyuti Pandya (European Centre for International Political Economy (ECIPE), 2025)
Cloud computing underpins digital transformation and is essential for unlocking the benefits of artificial intelligence (AI), automation, and scalable digital services. Yet Europe continues to lag behind global peers in both cloud and AI adoption. This underperformance is not merely technological; it is structural and it is costly. Without rapid progress, the EU risks missing out on over EUR 1.2 trillion in GDP gains across the private sector by around 2030. In the public sector alone, a shift to cloud particularly via a multi-cloud-first strategy could generate up to EUR 450 billion annually in efficiency and productivity gains across EU governments. A major, yet under-recognised barrier is the lack of cloud customer choice, the ability for businesses and public sector users to freely select, combine, and switch between cloud services. Without this, users face high switching costs, vendor lock-in, and reduced capacity to scale or integrate AI tools effectively. This paper asks: What are the main obstacles to cloud customer choice in the EU and what are the best avenues for advancing it? The analysis focuses on three key domains that shape the market at large - regulation, competition policy, and standard-setting bodies - examining how each can promote broader customer choice rather than be used narrowly to target individual, innovation-driven firms.
Keywords: 330